Mark-Recapture and Stochastic Population Models for Polar Bears of the High Arctic - Taylor, Mitchell K.; Laake, Jeff; McLoughlin, Philip D.; Cluff, H. Dean; Messier, Francois (ARCTIC, 2009)
We used mark-recapture data and population viability analysis (PVA) to estimate demographic parameters, abundance, and harvest risks for two adjacent populations of polar bears (Ursus maritimus) inhabiting Lancaster Sound and Norwegian Bay, Canada. Analyses were based on data from 1871 bears that were uniquely marked during the period 1972–97. Our best-fitting mark-recapture model specified sex and age effects on probabilities of survival and an effect of prior recapture (dependence) on capture probability. The most parsimonious solution in our analysis of survival was to assume the same rate for the Lancaster Sound and Norwegian Bay populations. Total (harvested) annual survival rates (mean ± 1 SE) for females included: 0.749 ± 0.105 (cubs), 0.879 ± 0.050 (ages 1–4), 0.936 ± 0.019 (ages 5– 20), and 0.758 ± 0.054 (ages 21+). Mean litter size was 1.69 ± 0.01 cubs for females of Lancaster Sound and 1.71 ± 0.08 cubs for females of Norwegian Bay. By age six, on average 0.31 ± 0.21 females of Lancaster Sound were producing litters (first age of reproduction was five years); however, females of Norwegian Bay did not reproduce until age seven or more. Total abundance (1995–97) averaged 2541 ± 391 bears in Lancaster Sound and 203 ± 44 bears in Norwegian Bay. The finite rate of increase (lambda) during the study period was estimated to be 1.001 ± 0.013 for bears of Lancaster Sound and 0.981 ± 0.027 for bears of Norwegian Bay. We incorporated demographic parameters into a harvest-explicit PVA to model short-term (15 yr) probabilities of overharvesting (i.e., 1997–2012). Our harvest simulations suggest that current levels of kill are approaching and perhaps exceeding the sustainable yield in both populations. Nous avons recouru aux données obtenues par marquage et recapture ainsi qu’aux analyses de viabilité de population pour estimer les paramètres démographiques, l’abondance et les risques liés à la récolte de deux populations adjacentes d’ours polaires (Ursus maritimus) évoluant dans le détroit de Lancaster et la baie ...